New developments in ICRF antennas and non-traditional applications of HF power on TEXTOR - Lyssoivan, A.; Messiaen, A.; Koch, R.; Durodié, F.; Amarante-Segundo, G.S.; Dumortier, P.; Van Eester, D.; Vervier, M.; Weynants, R.; Esser, H.G.; Gauthier, E.; Hoekzema, F.; et al. (Вопросы атомной науки и техники, 2002)
This paper reviews the present status of new developments in ICRF antennas, recent results on more realistic modeling of ICRF antennas using the 3-D full electromagnetic code ICANT and, finally, the latest development in the scenarios of non-traditional applications of HF power for wall conditioning.